Using Muscle Strength And Tissue Adaptation To Treat Patellofemoral Pain Syndrome Without Subjecting The Body To Strenuous Exercise - Priyanka Lizy Jeba (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
Patellofemoral pain syndrome (PFPS) is the collective term for pain that arises in the patellofemoral joint itself or in the surrounding soft tissues. Blood flow restriction (BFR) training has emerged as a popular and promising technique to increase muscle strength and promote tissue adaptability without subjecting the body to demanding activity. Pilates generates muscular stress through a series of basic, repetitive activities. The study's main objective is to evaluate how well Pilates-based exercises and blood flow restriction training work to improve function and lessen discomfort in people with patellofemoral pain syndrome. As observation subjects, thirty patients with a diagnosis of patellofemoral pain were chosen at random and split into two groups. The course of treatment lasted three months, with three sessions per week. The Numerical Pain Rating Scale (NRS) and the Anterior Knee Pain Scale were compared and analyzed in this study. The NRS score of the knee and the Anterior Knee Pain Scale were compared and examined in this study before and after treatment. Following treatment, Group A's functional status and health-related quality of life significantly improved in comparison to Group B, and Group A's pain intensity significantly decreased. The study's findings show that Pilates-based core strengthening exercises can help teens with PFPS in a variety of ways, including pain reduction, improved functional status, and improved quality of life.